Meteorologists - Hammonds, Heather. frey50 (North Mankato, Minn. : Smart Apple Media, 2005)
Provides information related to becoming a meteorologist, the education needed, the tools used, and the circumstances in which they work.
Includes bibliographical references and index
Keywords: Meteorology -- Vocational guidance; Meteorologists; Meteorologists; Meteorology -- Vocational guidance; Vocational guidance